South-South Trade: An Asian Perspective - Prema-Chandra Athukorala (Asian Development Bank (ADB), 2011)
The purpose of this paper is to inform the contemporary policy debate on promoting trade among developing countries (South–South trade) by analyzing trade patterns of developing Asian economies from a comparative global perspective. The paper begins with a stage-setting historical overview of the policy debate on South–South trade. It then examines trends and patterns of South–South trade in Asian economies, with emphasis on the implications of the growing importance of global production sharing and the rise of the People's Republic of China, followed by an econometric analysis of the determinants of South–South trade flows within the standard gravity modeling framework. As far as developing Asian countries are concerned, there is no evidence to suggest that growth of their trade with the Southern trading partners has lagged behind what we would expect in terms of the standard determinants of trade potential. The findings also suggest that South–South trade is largely complementary to, rather than competing with, South–North trade.
hdl:11540/2018
Keywords: F10; F13; F14; O53; 330; South-south trade; gravity model; global production; Asia; Peoples Republic of China; Latin America; Internationale Wirtschaft; Asien; Internationale Wirtschaftsbeziehungen; Lateinamerika; Afrika; Mittlerer Osten